EFFECT OF DEBT POLICY, DIVIDEND POLICY AND OWNERSHIP OF COMPANY PERFORMANCE - Frendi Frendi (Business and Entrepreneurial Review, 2010)
The background of this research is prior empirical researches about firm performance analysis have no consistent result. This research is based on the research in Kuala Lumpur by Ahmed(2008). The objectives of this research are to analyze the impact of debt policy, dividend policy, and corporate ownership which consist of management ownership and institutional ownershipon firm performance. The design of this research applies the impact of independent variable on dependent variable. The independent variable in this study are debt policy, dividend policy,managerial ownership, and institutional ownership. The dependent variable is firm performance. This study based on a sample of 13 firms that listed in Indonesia Stock Exchange LQ-45 during 2005 – 2008. This research uses ratio scale. Data analysis applied measuring method on multiple regression model and uses SPSS for windows to examine the impact of independent variables on dependent variable. The result of result indicated that dividend policy has significant impact on firm performance, whereas debt policy and corporate ownership have no significant impact on firm performance